Best practices for a sustainable energy sector at European Union level: Chances and challenges for Romania - Adrian Dumitru Tanţău; Ana-Maria Iulia Şanta (Amfiteatru Economic Journal, 2019)
Sustainability is a trend reflected nowadays both at global level and at European Union level. This applies as well to the energy policy sector, which is being modernized considering the sustainable use of resources. This trend finds its concrete expression in the package "Clean Energy for All Europeans" adopted by the European Commission in 2016, containing measures for a modernized energy sector of the European Union, based on an Energy Union, on clean energy and renewable energies and on energy efficiency. Measures in order to build a legal an institutional framework supporting the achievement of these goals are designed in this package. The idea of a harmonized energy sector of the European Union developed in time in the past twenty years, with several steps performed in this direction. The energy sector has been liberalized, competition rules have been applied considering consumer welfare as well the development of a new and innovative business environment. The consumer focus as a novelty in the design of energy policy is gaining more and more importance. The present paper deals with best practices related to the developments of a sustainable energy sector at European Union level, assessing as well new perspectives, chances and challenges arising for Romania in this context. Case studies illustrate these issues in a comparative manner, using an interdisciplinary approach based on mixed methods and integrating aspects of business, economics, European Union Law and European policies.
Keywords: Q01; Q20; Q40; Q42; Q47; 330; best practices; sustainable energy sector; energy policy; Clean Energy